Bilateral epididymal metastases from primary adenocarcinoma of the prostate - Gaskin, D A; Shah, D (West Indian medical journal, 2003)
A 65-year-old man diagnosed with adenocarcinoma of the prostate gland opted for hormonal manipulation and had bilateral orchiectomy. Histological evaluation showed tumour deposits in both epididymides. Despite the relatively common occurrence of adenocarcinoma of the prostate, epididymal metastasis is a rare occurrence. This case highlights the need for proper evaluation of the testes and para-testicular structures so that accurate staging of these tumours can be made.